Single-shot carrier-envelope-phase-tagged ion-momentum imaging of nonsequential double ionization of argon in intense 4-fs laser fields - Johnson, Nora G.; Herrwerth, O.; Wirth, A.; De, S.; Ben-Itzhak, I.; Lezius, M.; Bergues, B.; Kling, M. F.; Senftleben, A.; Schröter, C. D.; Moshammer, R.; Ullrich, J.; et al. (My University, 2011)
Single-shot carrier-envelope-phase (CEP) tagging is combined with a reaction mircoscope (REMI) to investigate CEP-dependent processes in atoms. Excellent experimental stability and data acquisition longevity are achieved. Using this approach, we study the CEP effects for nonsequential double ionization of argon in 4-fs laser fields at 750 nm and an intensity of 1.6×1014 W/cm2. The Ar2+ ionization yield shows a pronounced CEP dependence which compares well with recent theoretical predictions employing quantitative rescattering theory [S. Micheau et al., Phys. Rev. A 79, 013417 (2009)]. Furthermore, we find strong CEP influences on the Ar2+ momentum spectra along the laser polarization axis.